Analysis of Production Management at PT Maha Putra Jaya: Challenges and Strategies for Increasing Efficiency - Lestari, Sri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This research aims to analyze production management at PT Maha Putra Jaya with a focus on the challenges faced and strategies to increase efficiency. PT Maha Putra Jaya, as a manufacturing company, faces various issues in its production process, including low machine efficiency, product quality problems, and workforce training needs. The research methods used include interviews with production managers, direct observation on the production floor, and analysis of related documents. Key findings show that machine efficiency is compromised by a lack of preventive maintenance, product quality often does not meet standards due to suboptimal quality control, and employee training is inadequate to support the required skills. The research recommends implementing more stringent preventive maintenance systems, improvements in quality control techniques such as Six Sigma, and the development of more comprehensive training programs. By implementing these strategies, it is hoped that PT Maha Putra Jaya can increase production efficiency and product quality significantly.